1979
DOI: 10.1161/01.str.10.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electrical and mechanical responses of isolated rabbit pial arteries to some vasoactive drugs.

Abstract: SUMMARY Simultaneous measurements were made of spike activity and perfusion pressure (P A ) in intact segments of rabbit middle cerebral artery in vitro. The segments were mounted on a Teflon tube designed so that the perfusing solution flowed in the annular space between the tube and the artery wall, thus magnifying the P A changes occurring when the artery constricted or dilated. A widened portion of the Teflon tube immobilized 1-2 mm of the artery segment for electrical recording with fine glass microelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…In contrast, serotonin depolarized and contracted both vessels. Lusamvuku et al (1979) also found spike frequency in the middle cerebral artery of the rabbit correlated with tension generated by norepinephrine. Application of tetraethylammonium chloride (TEA), which suppresses K + permeability, does not change membrane potential in the basilar artery but evokes spike potentials upon application of norepinephrine (Harder et al 1981).…”
Section: In Vitro Studiesmentioning
confidence: 80%
“…In contrast, serotonin depolarized and contracted both vessels. Lusamvuku et al (1979) also found spike frequency in the middle cerebral artery of the rabbit correlated with tension generated by norepinephrine. Application of tetraethylammonium chloride (TEA), which suppresses K + permeability, does not change membrane potential in the basilar artery but evokes spike potentials upon application of norepinephrine (Harder et al 1981).…”
Section: In Vitro Studiesmentioning
confidence: 80%
“…16 - 17 The cerebral arterioles were unresponsive to isoproterenol, 1415 whereas the cheek pouch arterioles responded with an intense vasodilation. Since Wahl et al 15 demonstrated that isoproterenol did not produce any significant changes in the diameters of pial arterioles in cats, this supports the present evidence that the grafted cerebral tissue and its microvasculature remained pharmacologically intact; thus, the microvessels of the cerebral allograft did not dedifferentiate to pharmacologically mimic cheek pouch arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…The newest approach being used to study arteries in vitro entails the cannulation of whole cylindrical sections of vessel between rigid tubes which are perfused both intraluminally and extraluminally with modified Krebs solution [Lusamvuku et al, 1979;Schabert et al, 1980;Vinall and Simeone, 1981;Forstermann et al, 1984]. This method produces less cellular damage due to cutting than both the helical and ring meth ods, while duplicating levels of pressure and flow that more closely mimic in situ condi tions.…”
Section: Introductionmentioning
confidence: 99%